1980
DOI: 10.1063/1.328108
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum ultraviolet absorption cross sections for halogen containing molecules

Abstract: Vacuum ultraviolet absorption cross sections for the compounds Cl2, Br2, I2, HCl, HBr, HI, CCl4, CCl3Br, CF3Br, CF3I, HgCl2, HgBr2, and HgI2 have been measured between 170 and 230 nm. Studies of the Xe*2 discharge lamp used are reported. The absorption bands of various mercuric halides are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
19
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 19 publications
7
19
0
Order By: Relevance
“…In general, the precision and accuracy of the present measurements was better than obtained in previous CCl 4 cross section studies. A comparison of the present results at each wavelength with the previously reported values (Burton et al, 1994;Causley and Russell, 1977;Gillotay and Simon, 1990;Gordus and Bernstein, 1954;Ho, 1998;Hubrich and Stuhl, 1980;Ibuki et al, 1986;Prahlad and Kumar, 1995;Rowland and Molina, 1975;Roxlo and Mandl, 1980;N. Rontu Carlon et al: N 2 O and CCl 4 UV cross sections Seccombe et al, 1999;Simon et al, 1988;Vanlaethem-Meurée et al, 1978) is shown in Fig.…”
Section: Comparison With Previous Studiessupporting
confidence: 73%
See 1 more Smart Citation
“…In general, the precision and accuracy of the present measurements was better than obtained in previous CCl 4 cross section studies. A comparison of the present results at each wavelength with the previously reported values (Burton et al, 1994;Causley and Russell, 1977;Gillotay and Simon, 1990;Gordus and Bernstein, 1954;Ho, 1998;Hubrich and Stuhl, 1980;Ibuki et al, 1986;Prahlad and Kumar, 1995;Rowland and Molina, 1975;Roxlo and Mandl, 1980;N. Rontu Carlon et al: N 2 O and CCl 4 UV cross sections Seccombe et al, 1999;Simon et al, 1988;Vanlaethem-Meurée et al, 1978) is shown in Fig.…”
Section: Comparison With Previous Studiessupporting
confidence: 73%
“…The different be- Simon et al (1988), the data set currently recommended by JPL06-2 (Sander et al, 2006) for use in atmospheric modeling, are plotted using the cross section and temperature dependence parameterization reported in their work. Data from Causley and Russell (1977), Seccombe et al (1999), Ho (1998), and Roxlo and Mandl (1980) are not included due to the large deviation from the other studies.…”
Section: Uv Absorption Cross Sectionsmentioning
confidence: 99%
“…J. C. Gómez Martín et al: In situ detection of atomic and molecular iodine using ROFLEX There are a number of molecules (dihalogens and interhalogens) with an analogous structure of electronic states, which could absorb photons and emit fluorescence in the same spectral range in which the lamp emits. However, the absorption cross section of the I 2 ion-pair ← X band between 178 nm and 210 nm is at least one order of magnitude larger than the ion-pair ← X cross sections of any other dihalogen or interhalogen (Roxlo and Mandl, 1980;Yencha et al, 1988;Hopkirk et al, 1989;Lawley et al, 1990). Therefore, significant ion-pair → A fluorescence of other dihalogens and interhalogens in the 300-400 nm can hardly be expected under atmospheric conditions.…”
Section: Molecular Iodinementioning
confidence: 99%
“…Molecular iodine presents a strong, highly structured absorption feature in the same spectral region (170 nm-210 nm), known as the Cordes bands (D ← X system), with absorption cross sections of ∼ 2 × 10 −17 cm 2 molecule −1 at 188 nm (0.14 nm FWHM) (Myer and Samson, 1970;Roxlo and Mandl, 1980;, Fig. 1b.…”
Section: Principle Of Resonance and Off-resonance Fluorescence By Lammentioning
confidence: 99%
See 1 more Smart Citation